Labor market regulation and gendered entrepreneurship: a cross-national perspective. - Angulo-Guerrero, María José; Bárcena-Martín, Elena María; Medina-Claros, Samuel; Pérez-Moreno, Salvador Jesús (Springer Nature, 2023)
This research examines the extent to which labor regulatory context matters for entrepreneurial activity under a gender perspective, using institutional economics and feminist theories as the analytical framework. We conduct a panel data analysis for 86 countries during the period 2004- 2018 by differentiating between high-income and developing economies. Our findings highlight that while the links between labor regulation and entrepreneurial activity seem negligible in high-income economies, in developing economies labor flexibility is closely associated with female entrepreneurship. However, unlike the market-oriented view on the positive association between labor market flexibility and entrepreneurship, our results point out that in these economies more flexible labor regulation is related to lower early-stage female entrepreneurial activity, even though this relationship tends to vanish as the level of economic development of the country increases. This study contributes theoretically, helping to advance the analysis of gender differences in entrepreneurial activity from an institutional approach, and practically, providing evidence to policy makers on possible gender differences in the application of country-level labor market regulation in terms of entrepreneurial activity.
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/16452
Keywords: Mercado de trabajo; Emprendedores; Empresarias; Labor market regulation; Entrepreneurship; Gender; Cross-country analysis